A 2.5-D coupled FE–BE model for the dynamic interaction between saturated soil and longitudinally invariant structures. (February 2017) - He, Chao; Zhou, Shunhua; Di, Honggui; Shan, Yao
Abstract: A two-and-a-half-dimensional (2.5-D) coupled finite element–boundary element (FE–BE) model is presented to simulate the three-dimensional dynamic interaction between saturated soils and structures with longitudinally invariant geometries. A regularized 2.5-D boundary integral equation for saturated porous media is derived that avoids the evaluation of singular traction integrals. The 2.5-D coupled FE–BE model is established by using the continuity conditions on the soil–structure interface. The developed model is verified through comparison with an existing semi-analytical method. Two case studies of a tunnel embedded in a poroelastic half-space and the efficiency of a vibration isolating screen are presented.